Study of fusion neutron yield from PF-360 facility equipped with solid-state or gas-puffed targets - Zebrowski, J.; Baranowski, J.; Jakubowski, L.; Sadowski, M.J.; Stanislawski, J. (Вопросы атомной науки и техники, 2000)
The paper reports on results of Plasma-Focus (PF) investigation carried out within the PF-360 device, which was equipped with exchangeable targets made of heavy-ice (D2O) layers or D2-gas puffs. The main aim of these studies was to increase a neutron yield from PF discharges by using fast deuteron beams, which are usually emitted from a pinch column and which can interact with additional targets.